A review of impact climate change on food security - Abdullah, Nor Maizzaty; Mohd Arish, Nur Aini; Hamidon, Nuramidah; Hashim, Nor Haslina; Ali, Roslinda; ., Ain Nadhirah; ., Nafratiti Najiha (Penerbit UTHM, 2020)
Climate change is long-term alteration of temperature that cause the patterns of weather is less predictable. When the weather cannot be unexpected, it is difficult to maintain the crops. The impact is comprehensive but it is far reaching clearly visible on agricultural sector, on which the food production and economy of the world. Agriculture provides the primary sources of livehood for 36 percent of the world.